PENGARUH PENUNDAAN PENANGANAN SPUTUM TERHADAP HASIL PEMBACAAN SEDIAAN SECARA MIKROSKOPIS PADA PENDERITA TB DI UPT. LABORATORIUM KESEHATAN DAERAH PROVINSI SUMATERA UTARA - Nelma, Nelma; Lumbantoruan, Armida (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2019)
The background of the study is whether there are differences in the results of microscopic smear reading and the quality of direct sputum preparations, check with sputum 24 hours at room temperature. The purpose of the study was to determine the effect of delaying the handling of sputum on the results of microscopic readings of preparations in tuberculosis patients. Type of descriptive observation research. Research time June 2019. Research location at the Regional Health Laboratory of North Sumatra Province. The results showed that from 16 sputum samples that were immediately examined, the scanty results were 2 samples, 1+ there were 2 samples, 2+ there were 2 samples, 3+ there were 10 samples, whereas in the 24 hour sample at room temperature, there were 2 negative results, 1+ there are 4, 2+ there are 3, and 3+ there are 7 samples of BTA. Of the 16 sputum, they were immediately examined by delaying 24 hours at room temperature, 7 sputum were obtained, the results of which were reduced. There is no positive number added, the same number of positive results is 9 sputum. This suggests that a 24-hour delay in sputum examination at room temperature can result in false positives. There are differences in the results between sputum directly checked by being delayed 24 hours at room temperature 25?C. It is recommended that an AFB sputum be examined immediately to avoid the results of false negative smear microscopic examination.